Meglumine Sodium Succinate to Correct COVID-19-Associated Coagulopathy: the Feasibility Study - I. S. Simutis (Obŝaâ Reanimatologiâ, 2021)
Aim of the study: to evaluate the effect of meglumine sodium succinate (MSS) on the efficacy of anticoagulant therapy in patients with severe COVID-19 infection complicated by bilateral community-acquired pneumonia.Materials and methods. Overall efficacy of treatment was analyzed in 12 patients hospitalized to ICU with the diagnosis of severe confirmed COVID-19 coronavirus infection (U07.1) complicated by bilateral multisegmental pneumonia. All patients received prophylactic anticoagulation with unfractionated heparin. The patients were divided into two groups: 7 of them received a multi-electrolyte solution containing MSS 5 ml/kg daily for the entire ICU stay (3-10 days) as a part of therapy; 5 patients received a similar volume of a conventional multi-electrolyte solution containing no metabolically active substrates and comprised a control group. Coagulation parameters were measured in arterial and venous blood of all patients at the following stages: 1) upon admission to the ICU; 2) 2-4 hours after the first dose of heparin; 3) 8-12 hours after the second dose of heparin; 4) 24 hours after the beginning of intensive therapy. On the 28th day of follow-up, mortality, duration of ICU stay, and incidence of thrombotic complications in the groups were evaluated. Nonparametric methods of statistical analysis were used to assess intragroup changes and intergroup differences.Results. The group of patients administered with MSS had significantly fewer thromboembolic events during 28 days of treatment and shorter ICU stay. These patients responded faster to anticoagulant therapy, which was suggested by more distinct changes in coagulation parameters, i.e. increased APTT, persisting viable thrombocyte population, reduced D-dimer and fibrinogen levels.Conclusion. The metabolic action of succinate possibly increases endothelial resistance to damaging factors and reduces its procoagulant activity. The hypothesis requires testing in a larger clinical study with a design including laboratory evaluation of the efficacy of varying doses of the studied drug as well as aiming at elucidation of the mechanisms of its effect on specific pro- and anticoagulation system components.